Implementing ISO/FSSC 22000 - Food Safety Management System in a SME - Granholm, Camilla (My University, 2017)
The purpose of this thesis was to find out how to implement a food safety management system, ISO/FSSC 22000, in a small and medium sized enterprise. The thesis work was carried out in parallel with the starting of implementation in a case company. During the course of the thesis the secondary purpose was to find out the benefits and challenges for implementing a quality system such as this. The theoretical framework includes main concepts such as quality management, continuous improvement and document management. The theory part also presents the concept of ISO 22000 and FSSC 22000 and main aspects to consider in case implementing other quality systems in retrospect. The main method in the empirical part is literature review, to understand the food safety management system standards and requirements. Benchmarking has also been performed to create a better picture of how other companies within this branch has experienced the implementation. The main result of the thesis was a guideline for how to implement and what to consider when acquiring the ISO or FSSC 22000 certificate.
Keywords: Quality Management; Quality Management System; Food Safety Management System; fi=Tuotantotalous|en=Industrial Management|; fi=Master's Degree Programme in Industrial Management|